2021
DOI: 10.1302/2046-3758.105.bjr-2020-0020.r1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from mesenchymal stem cells containing microRNA-381 protect against spinal cord injury in a rat model via the BRD4/WNT5A axis

Abstract: Aims Non-coding microRNA (miRNA) in extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) may promote neuronal repair after spinal cord injury (SCI). In this paper we report on the effects of MSC-EV-microRNA-381 (miR-381) in a rodent model of SCI. Methods In the current study, the luciferase assay confirmed a binding site of bromodomain-containing protein 4 (BRD4) and Wnt family member 5A (WNT5A). Then we detected expression of miR-381, BRD4, and WNT5A in dorsal root ganglia (DRG) cells treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The process of study selection is outlined in Figure 1 . A total of 153 articles were identified, of which 11 articles satisfied the inclusion criteria ( Ji et al, 2019 ; Kang et al, 2019 ; Yu et al, 2019 ; Kang et al, 2020 ; Liu et al, 2020 ; Wang et al, 2020 ; Jia et al, 2021 ; Jiang and Zhang, 2021 ; Zhang L. et al, 2021 ). After deleting duplicate articles, we excluded 74 irrelevant articles (e.g., irrelevant disease models, reviews, and conferences) by examining the title and abstract of the article.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of study selection is outlined in Figure 1 . A total of 153 articles were identified, of which 11 articles satisfied the inclusion criteria ( Ji et al, 2019 ; Kang et al, 2019 ; Yu et al, 2019 ; Kang et al, 2020 ; Liu et al, 2020 ; Wang et al, 2020 ; Jia et al, 2021 ; Jiang and Zhang, 2021 ; Zhang L. et al, 2021 ). After deleting duplicate articles, we excluded 74 irrelevant articles (e.g., irrelevant disease models, reviews, and conferences) by examining the title and abstract of the article.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported intravenous administration of the same dose of exosomes (100 μg, 200 µg). The studies used many different miRNAs to modify exosomes, including miR-26a ( Chen et al, 2021 ), miR-126 ( Huang et al, 2020 ), miR-145-5p ( Jiang and Zhang, 2021 ), miR-381 ( Jia et al, 2021 ), miR-21 ( Ji et al, 2019 ; Kang et al, 2019 ), miR-216a-5p ( Liu et al, 2020 ), miR-421-3p ( Wang et al, 2020 ), miR-29b ( Yu et al, 2019 ) and miR-181c ( Zhang M. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we introduced the involvement of lncRNAs and miRNAs through the Rho/ROCK pathway in IS and SCI and the potential therapeutic effects of the intervention with these ncRNAs. The clinical utility of miRNAs will be very high if they can be delivered in the form of extracellular vesicles, as shown by Jia et al [ 123 ]. Because previous studies on the relationship between the Rho/ROCK pathway and ncRNAs in IS and SCI were only related to apoptosis, neuroinflammation, oxidative stress, and axonal regeneration, future studies are expected to include BBB integrity, astrogliosis, neurogenesis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are candidates for the vehicles of bioactive molecules, such as mRNA, miRNAs, and lncRNAs, and EVs derived from various cells are thus expected to be a potential therapeutic method. Jia et al investigated whether miR-381 encapsulated in the EVs derived from mesenchymal stem cells (MSCs) can promote the recovery of SCI [ 123 ]. MiR-138 is essential for the proliferation of nerve cells during SCI.…”
Section: Rho/rock Pathway and Mirnas For Apoptosis/axon Regeneration In Scimentioning
confidence: 99%